Efficacy and safety of PD-1/PD-L1 inhibitor-based immune combination therapy versus sorafenib in the treatment of advanced hepatocellular carcinoma: a meta-analysis - She, Mingjin; Wu, Yayun; Cheng, Mengmeng; Feng, Sanli; Li, Guizhi; Rong, Hui (Frontiers in Medicine, 2024)
Objective To systematically evaluate the safety and efficacy of PD-1/PD-L1 inhibitor-based immunotherapy (hereafter referred to as “combination immunotherapy”) compared with that of sorafenib in the treatment of hepatocellular carcinoma (HCC). Methods Databases such as PubMed, Embase, and the Cochrane Library were searched from the date of their establishment to September 2023 to identify randomized controlled trials (RCTs) of combination immunotherapy versus sorafenib for the treatment of advanced HCC. Two reviewers independently evaluated the quality of the included studies, extracted the data, and cross-checked the information. The meta-analysis was performed using RevMan 5.3 software. Results A total of 5 RCTs were included. The results of the meta-analysis showed the following: (1) Effectiveness. Compared to sorafenib, combination immunotherapy significantly improved overall survival (OS, HR = 0.69, 95% CI: 0.58 0.82, p < 0.01) and progression-free survival (PFS, HR = 0.62, 95% CI: 0.50 0.78, p < 0.001) in patients with advanced HCC. (2) Safety. Both groups had comparatively high incidences of adverse events (AEs), but the difference in any treatment-related adverse events was not significant between the two arms (OR = 0.98, 95% CI: 0.95 1.02, p = 0.34). The difference in the incidence of grade 1–2 adverse reactions was statistically significant (OR = 0.66, 95% CI = 0.49–0.90, p = 0.001). There were no differences in grade 3/4 TRAEs or grade 5 TRAEs (OR = 1.46, 95% CI = 0.78 2.71, p = 0.24; OR = 1.08, 95% CI = 0.73 1.58, p = 0.71). Conclusion Combined immunotherapy can significantly prolong the OS and PFS of patients with advanced HCC without increasing the incidence of adverse effects in terms of safety, but the incidence of AEs in different systems is different.